(untitled) (Scientific journal of the Fergana State University, 2024)
Organic reagents were selected for determination of gallium and aluminum ions by sorption-spectroscopic method. Oxyazocompounds and polyoxyflavones were found to be the most effective for this process. The optimal conditions for reacting the reagents with ions of the studied metals were selected. Possibilities of immobilization of oxyazocompound and polyoxyflavone reagents to various carriers were investigated. The mechanism of immobilization and its effect on luminescence were elucidated.